The Relationship between Mother's Education Level and the Regularity of Pregnancy Check-ups at Gandasuli Community Health Center, South Bacan District, South Halmahera Regency, North Maluku Province - Illa Kurnia Ikhtiar; Anik Sri Purwanti (International Forum of Researchers and Lecturers, 2026)
Background: Regular antenatal care is essential to ensure maternal and fetal health during pregnancy and to prevent complications. The level of maternal education plays an important role in shaping health knowledge, attitudes, and behaviors related to pregnancy care. Mothers with higher education levels tend to have better awareness and understanding of the importance of routine pregnancy check-ups. However, irregular antenatal visits are still found in several regions, including the working area of the Gandasuli Community Health Center, South Bacan District, South Halmahera Regency, North Maluku Province.Objective: This study aimed to analyze the relationship between mother’s education level and the regularity of pregnancy check-ups at the Gandasuli Community Health Center, South Bacan District, South Halmahera Regency, North Maluku Province.Methods: This study employed a quantitative analytical design with a cross-sectional approach. The sample consisted of 30 pregnant women selected using a total sampling technique. Data were collected using structured questionnaires and maternal health records to assess education level and the regularity of antenatal care visits. Data analysis was performed using the Wilcoxon test.Results: The results of the Wilcoxon test showed a significant relationship between mother’s education level and the regularity of pregnancy check-ups, with a p-value of 0.000 (p < 0.05). Conclusion: There is a significant relationship between mother’s education level and the regularity of pregnancy check-ups at the Gandasuli Community Health Center. Improving maternal education and strengthening health education programs are essential to increase compliance with routine antenatal care visits and improve maternal and fetal health outcomes.